Prevalence Of Low Back Pain Among Medical Students Post Covid-19 Pandemic In 2023 - Maria, Ima; Yanti Harjono; Yuli Suciati; Raja Soaloon Purba; Muhammad Gifta Utomo (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
ABSTRACT Background: Epidemiological studies indicate that low back pain (LBP) is not only experienced by the elderly but also affects the younger population. The presence of LBP in medical students can impact their functionality and daily practices after graduation. This study aims to provide an overview of the prevalence of LBP among medical students at the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta. Methods: The study included a total of 738 subjects representing clinical and four levels of undergraduate programs. The Nordic questionnaire and the Oswestry Disability Index (ODI) were employed to assess LBP and its impact on daily life. Results: The prevalence of LBP was 61.2%, with 6.6% experiencing moderate disability. Gender, exercise habits, and a family history of LBP were statistically significant. Conclusion: Institutions need to implement interventions to mitigate LBP among medical students.